ANALISIS HUBUNGAN PERSEPSI BAURAN PEMASARAN DENGAN MINAT PETANI DALAM KEPESERTAAN BPJS KESEHATAN MANDIRI DI KECAMATAN PRACIMANTORO KABUPATEN WONOGIRI - Manja Mania; Sutopo Patria Jati; Eka Yunila Fatmasari (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
The membership aspect is an indicator of the success of BPJS Health. Farmers as one of the majority workers in Kecamatan Pracimantoro, thus contributing greatly in the membership BPJS Health. Preliminary study results show up to January 2017 household farmers who have been registered in the PBI amounted to 8,505 KK so that about 9,554 KK contribute in the independent participation. The purpose of this research is to know the description farmer interest and analyze factors related to farmer interest in participation of independent health BPJS through perception about marketing mix. This research uses quantitative method and cross sectional research type with sample of 100 farmers in Pracimantoro District, Wonogiri Regency. The results showed that the majority of farmers in Pracimantoro District are less interested in the participation of independent health BPJS (58%). The result of bivariate analysis shows that there is correlation between perception about product (Independent health BPJS) (p = 0,038), perception about premium price (p = 0,009), perception about promotion (p = 0,008) with farmer interest of independent health BPJS. While unrelated factors were perception about location (p = 0,360). It is recommended to health BPJS to increase promotion especially for farmers in rural areas that are difficult to reach. So farmers understand the concept of BPJS and willing to volunteer to register in the participation of independent health BPJS.